Peran Bioteknologi Probiotik Asal Dadih Sumatera Barat terhadap Performa Produksi Itik Lokal Sumatera Barat - Hendri Purwanto; Zulkarnain Zulkarnain (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2025)
Probiotics from West Sumatra curd have the potential to improve the production performance of local West Sumatra ducks, where Probiotics are live bacteria given as food sulpementation. Giving probiotics can have a beneficial effect on health where probiotics produce inhibitor compounds so that they can maximize the absorption of food in the intestines of livestock. The purpose of this study was to observe the production performance of ducks given probiotics. The design used was a randomized complete factorial method. The first factor (A) Dosage of probiotics (LAB) is with treatment A1: 1 ml (12.7 x 108 CFU/g); A2: 2 ml (25.4 x 108 CFU/g); A3: 3 ml (38.1 x 108 CFU/g). The second factor (B) is the frequency of probiotic administration, namely B1: 0 times; B2: 1 time; B3: 2 times; B4: 3 times; B5: 4 times; B6: 5 times; B7: 6 times, consisting of 4 replicates with a total of 346 ducks. The observed variables were food consumption, body weight gain, ration conversion, carcass percentage. The results of this study were the average food consumption at a dose of 3 ml with 5 times administration (995.79g). The highest average body weight gain (369.74 grams) dose of 1 ml and 5 times administration. The highest carcass percentage with a dose of 3 ml and a frequency of 5 times (72.63%).